Design of the CO2 Removal Section for PSA Tail Gas Treatment in a Hydrogen Production Plant - Pellegrini, Laura A.; De Guido, Giorgia; Moioli, Stefania (Frontiers in Energy Research, 2020)
CO2 capture, storage, and, recently, utilization (CCSU) is considered effective in achieving the target of 2°C established to reduce the gradual increase in global warming. In the literature, most of research has focused on the removal of carbon dioxide from power plants, particularly those fed with coal, which account for higher amounts of CO2 emissions if compared with those fed with natural gas. CCSU in other non-power sectors is still not fully considered, while its importance in mitigating the environmental impact of industrial activities is equivalent to that of power plants. In the field of hydrogen production, treatment of gaseous streams to remove carbon dioxide is performed for producing a stream of almost pure H2 starting from syngas and for reducing carbon dioxide emissions, so that CO2 removal units can be part of different sections of the plant. In this work, a state-of-the-art steam-methane-reforming (SMR) plant for the production of 100,000 Nm3/h of hydrogen has been considered. Hydrogen is produced from syngas by employing the pressure swing adsorption (PSA) technology, and the exiting tail gas is fed to the burners of the SMR unit, after removal of carbon dioxide. This work focuses on the design of the units for the treatment of the PSA tail gas by employing an aqueous solution of methyldiethanolamine (MDEA). Simulations have been performed with the commercial process simulator ASPEN Plus®, customized by the GASP group of Politecnico di Milano for best representing both the thermodynamics of the system and the mass transfer with reaction. For the scheme composed of the absorber and the regenerator, several column configurations have been considered, and the optimal solution, which minimizes the energy requirements of the plant, has been selected.